"A GLARING OMISSION": BARRIERS TO INCLUDING LONG-TERM CARE RESIDENTS' VOICES IN THE NEWS MEDIA. (20th December 2022) - Allen, Laura; Bradley, Dana; Ayalon, Liat
Abstract: News media stories on residential long-term care (LTC) are mostly negative in tone, and the increase in news coverage of residential LTC during the COVID-19 pandemic intensified the pessimistic tone with panicked and accusatory reporting. Although there has been an increase in the amount of news coverage on residential LTC over the last two years, the perspectives of the residents themselves have been largely overlooked and excluded. The aim of this study is to identify and understand the barriers and embedded institutional logics in the news reporting process of LTC that prevent residents from being included and interviewed. Using a purposive sampling strategy, the researchers conducted 26 semi-structured interviews with LTC administrators (n=7), journalists on the topics of aging and LTC (n=7), and older residents living in LTC settings (n=12) in the United States. Thematic analysis is applied to the data to qualitatively extract the guiding logics frameworks of each stakeholder group. Findings are grouped into the following four themes: (1) residents are not considered "experts" by reporters and are therefore not a prioritized source of information; (2) facility administrators fear for the facility's public image & reputation and do not enthusiastically cooperate with inquiring reporters; (3) facilities were in physical lockdown for several months during the COVID-19 pandemic, and (4) residents feel forgotten and unheard. Implications of this study point to the social exclusion of older residents living in LTC and reductive reporting that fails to capture their nuanced and dynamic lived experiences.